FLORA AND FLORISTIC AFFINITIES OF THE CERRADOS OF MARANHÃO STATE, BRAZIL - Silva-Moraes, H. G.; Cordeiro, I.; Figueiredo, N. (Edinburgh Journal of Botany, 2018)
Cerrado vegetation is the main formation covering c.60% of the land surface of Maranhão, Brazil, with cerradão being the dominant physiognomy. To characterise the cerrado flora in Maranhão, 12 localities were selected across its distribution in the northeastern, central, southern and southeastern regions of the state. A total of 150 angiosperm species were identified, distributed across 105 genera and 43 families. Twelve are new occurrences in Maranhão, and of these, four are also new records for Northeast Brazil. Two distinct floristic regions were recognised: the cerrados of the northeastern and central regions, and the cerrados of the southern region. Three subgroups were recognised in the southern region: cerrados of the highest altitudes, medium-altitude cerrados and cerrados of variable altitudes. Floristic comparisons with the Brazilian cerrados suggest that the medium-altitude southern cerrados of Maranhão are similar to those of the central region of Brazil, whereas the northeastern, central and southern highest-altitude regions form a distinct floristic group.